Evaluation of BAPPEDA's Planning for Economic Transformation Towards the Industrialization Era - Revika Revika Viola Azzahara; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
This study aims to find out how to plan for Economic Transformation Towards the Industrialization Era in order to become the industrial sector with the greatest value in exporting. This research uses quantitative and qualitative methods. The sample in this study is to analyze 10 industries operating in North Sumatra Province. The results of the study indicate that in planning the transformation in the industrialization era there are several focuses that must be carried out for industries that are considered important and it is determined that human resource development in industry must be carried out properly and form a certain program and set a target to be achieved in the following year.